Liberals’ struggle with the problem of value pluralism - Mazur, Stanisław (Journal of Public Governance, 2018)
This paper aims to explore the approach to value pluralism within contemporary liberal political thought. The paper begins with a discussion of the basic premises related to both value pluralism and value conf lict. Then the author examines the successes of value pluralism theory in resolving value conf licts. The final section of the paper attempts to determine whether the liberal approach to value pluralism, protecting us against monism, is not leading us, at the same time, to value relativism.